The Implementation of Quiz Team Technique of Enhance Students’ Comprehension In Changing Active To Passive At SMA Negeri 8 Manado - Boham, Clarissa Enjelin; Muntuuntu, Meity; Rorimpandey, Rinny S (Program Studi Pendidikan Bahasa Inggris, 2024)
Abstract: This research aims to evaluate the use of Quiz Team Technique in enhancing students’ comprehension in changing active to passive voice at SMA Negeri 8 Manado. A quasi experimental design was used in this research, employing a quantitative approach. The subject of this research was class eleventh-grade students at SMA Negeri 8 Manado. Class XI C was an experimental class, while class XI D became a controlled class. Data were collected trough pre-test and post-test. The result of data analysis showed any difference between the total score of pre-test in experimental class was 1.050 and controlled class was 970. Meanwhile, in post-test showed the score of the experimental class was 2.610 and the controlled class was 1.945. This research calculated the effectiveness of Quiz Team Technique using SPSS version 26. The result showed that the effect of Quiz Team Technique with sig. (2 tailed) of .000 < .005. the alternative hypothesis (H1) was accepted, while the null hypothesis (H0) was rejected. Based on this research, it can be concluded that the use of Quiz Team Technique was considered effective in enhancing students’ comprehension in changing active to passive voice. Keywords: Quiz Team Technique, Enhance, Changing, Active Voice, Passive Voi ce